Emergency Medical Equipment Storage: Benefits of Visual Cues Tested in Field and Simulated Settings. (August 2014) - Grundgeiger, Tobias; Harris, Bonnie; Ford, Nicholas; Abbey, Michael; Sanderson, Penelope M.; Venkatesh, Balasubramanian
Objective: We tested the effectiveness of an illustrated divider ("the divider") for bedside emergency equipment drawers in an intensive care unit (ICU). In Study 1, we assessed whether the divider increases completeness and standardizes the locations of emergency equipment within the drawer. In Study 2, we investigated whether the divider decreases nurses' restocking and retrieval times and decreases their workload. Background: Easy access to fully stocked emergency equipment is important during emergencies. However, inefficient equipment storage and cognitively demanding work settings might mean that drawers are incompletely stocked and access to items is slow. Method: A pre-post-post study investigated drawer completeness and item locations before and after the introduction of the divider to 30 ICU drawers. A subsequent experiment measured item restocking time, item retrieval time, and subjective workload for nurses. Results: At 2 weeks and 10 weeks after the divider was introduced, the completeness of the drawer increased significantly compared with before the divider was introduced. The divider decreased the variability of the locations of the 17 items in the drawer to 16% of its original value. Study 2 showed that restocking times but not retrieval times were significantly faster with the divider present. For both tasks, nurses rated their workload lower with the divider. Conclusions: The divider improved the standardization and completeness of emergency equipment. In addition, restocking times and workload were decreased with the divider. Application: Redesigning storage for certain equipment using human factors design principles can help to speed and standardize restocking and ease access to equipment.